Evaluation of environmental magnetic pollution screening in soils of basaltic origin: results from Nashik Thermal Power Station, Maharashtra, India - Basavaiah, N.; Blaha, U.; Das, P.K.; Deenadayalan, K.; Sadashiv, M.B.; Schulz, H. (My University, 2012)
Background, aim, and scope Soils of basaltic origin cause difficulties in environmental magnetic screening for heavy metal pollution due to their natural high background values. Magnetic parameters and heavy metal content of highly magnetic topsoils from the Deccan Trap basalts are investigated to assess their potential for use in environmental magnetic pollution screening. This work extends the fast and cost-effective magnetic pollution screening techniques into soils with high natural magnetic signals. Materials and methods Fifty-five topsoil samples from N–S and W–E transects were collected and subdivided according to grain size using wet sieving technique. Magnetic susceptibility, soft isothermal remanent magnetization (Soft IRM), thermomagnetic analysis, scanning electron microscopy (SEM), and heavy metal analysis were performed on the samples. Results Magnetic analyses reveal a significant input of anthropogenic magnetic particulate matter within 6 km of the power plant and the adjacent ash pond. Results depend strongly on the stage of soil development and vary spatially. While results in the W, E, and S directions are easily interpretable, in the N direction, the contribution of the anthropogenic magnetic matter is difficult to assess due to high magnetic background values, less developed soils, and a more limited contribution from the fly ash sources. Prevailing winds towards directions with more enhanced values seem to have a certain effect on particulate matter accumulation in the topsoil. Thermomagnetic measurements show Verwey transition and Hopkinson peak, thus proving the presence of ferrimagnetic mineral phases close to the pollution source. A quantitative decrease of the anthropogenic ferrimagnetic mineral concentration with increased distance is evident in Soft IRM measurements. SEM investigations of quantitatively extracted magnetic particles confirm the fly ash distribution pattern obtained from the magnetic and heavy metal analyses. Evaluation of magnetic and chemical data in concert with the Pollution Load IndiceS (PLIS) of Pb, Zn, and Cu reveals a good relationship between magnetic susceptibility and the metal content. Conclusions Integrated approaches in data acquisition of magnetic and chemical parameters enable the application of magnetic screening methods in highly magnetic soils. Combined data evaluation allows identification of sampling sites that are affected by human activity, through the deviation of the magnetic and chemical data from the general trend. It is shown that integrative analysis of magnetic parameters and a limited metal concentration dataset can enhance the quality of the output of environmental magnetic pollution screening significantly.
Keywords: Basalt; Topsoil; Fly ash; Magnetic susceptibility; Metal contamination